Albania: Health Care System in the Course of Health Reform. An Overview of Health Insurance System - Kurti, Sllavka (Richtmann Publishing, 2011)
This paper introduces and analyses in general the Health Care System (HCS) focusing particularly on the Health InsuranceSystem (HIS) in Albania, as a country in a period of transition. The Government of Albania is in the process of reforming andmodernizing its healthcare sector and is moving towards the establishment of a more sustainable health financing insurance system. Theaim is to obtain a clear referential structure for the further development of the health insurance system and for the establishment ofeffective, managing and administrative capacities This paper is prepared by exploring the published literature and collecting data throughsecondary sources. Several data sources have been used to describe the health performance in Albania. The review includes severalreferences and, by covering OECD countries The concepts included here serve us to better know and understand the actual situation ofHIS, and what is more to be included in a â€œgeneral planâ€ for the preparation of the directives for the organization, implementation,observation and evaluation of the steps that have to be undertaken for the reformation of the health insurance in Albania. Albaniashould develop an explicit, comprehensive revenue collection strategy that considers all available methods, such as direct taxation, indirecttaxation, social security contributions, voluntary health insurance, and user charges, in order to optimize revenue collection.